Manganese Deficiency Is Required for High Itaconic Acid Production From D-Xylose in Aspergillus terreus - Kolláth, István S.; Molnár, Ákos P.; Soós, Áron; Fekete, Erzsébet; Sándor, Erzsébet; Kovács, Béla; Kubicek, Christian P.; Karaffa, Levente (Frontiers in Microbiology, 2019)
Itaconic acid is used as a bio-based, renewable building block in the polymer industry. It is produced by submerged fermentations of the filamentous fungus Aspergillus terreus from molasses or starch, but research over the efficient utilization of non-food, lignocellulosic plant biomass is soaring. The objective of this study was to test whether the application of two key cultivation parameters for obtaining itaconic acid from D-glucose in high yields – Mn2+ ion deficiency and high concentration of the carbon source – would also occur on D-xylose, the principal monomer of lignocellulose. To this end, a carbon and energy balance for itaconic acid formation was established, which is 0.83 moles/mole D-xylose. The effect of Mn2+ ions on itaconic acid formation was indeed similar to that on D-glucose and maximal yields were obtained below 3 µg L-1 Mn2+ ions, which were, however, only 0.63 moles of itaconic acid per mole D-xylose. In contrast to the case on D-glucose, increasing D-xylose concentration over 50 g L-1 did not change the above yield. By-products such as xylitol and α-ketoglutarate were found, but in total they remained below 2% of the concentration of D-xylose. Mass balance of the fermentation with 110 g L-1 D-xylose revealed that >95% of the carbon from D-xylose was accounted as biomass, itaconic acid and the carbon dioxide released in the last step of itaconic acid biosynthesis. Our data show that the efficiency of biomass formation is the critical parameter for itaconic acid yield from D-xylose under otherwise optimal conditions.